Effect of background colors on oviposition site preference by Anopheles gambiae s.s.: an experimental proof - Norah Lowassari; Germana T. Baraka; Grace Jayombo; Castory Munishi; Eliningaya J. Kweka (Academia Biology)
Background: Insecticide resistance and vector-feeding behavior changes have recently challenged malaria vector control. All this causes the vectors to forfeit the benefits of insecticide-based control tools. Searching for other control tools for immediate and future use is important. This study evaluated the gravid Anopheles gambiae s.s. response to habitat water with a background of different colors. Methods: Green, black, red, and blue were selected as background colors based on previous literature searches. The experiments were set up in a Latin square with drops out of colors and fewer eggs. Fresh habitat water was used on each experimental day. The egg count was done for two consecutive days. Results: The results of this study showed that the position of the oviposition substrate had no influence on gravid mosquito response. The highest number of eggs was laid on the green background in all stages of the experiments. The interaction of experimental days, position, and the number of eggs laid had no statistical significance. Conclusion: The findings of this study have shown that the habitat water coupled with a green-colored background influences most oviposition site selection by gravid An. gambiae. This shows that green-colored background can be integrated into the gravid mosquito traps for efficiency increase.